Analysis of the Principal’s Leadership Role on Cultural Development - Budi Sulistiyo Nugroho; Arkam Lahiya; Ardhana Januar Mahardhani; Anggara Setya Saputra; Handy Ferdiansyah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
Leadership is a process of influencing others towards achieving organizational goals. The most important aspect of the leadership process is the result of a complex series of interactions between the leader, the people being led, and the situation. This complex interaction can be directed to generalizations about leadership as something that is problematic as a factor influencing the leadership process. This must be supported by the appearance of the head of the madrasa. The appearance of the madrasa principal is determined by factors of authority, character and skills, behavior and flexibility of the madrasa principal. The results of the study concluded that Al-Ma'arif Boja School instilled the habit of speaking politely to the principal, teachers, staff and peers. The school also makes it a habit to smile and greet when meeting the principal, teachers, staff and friends. Schools also make it a habit to say hello when entering class, make it a habit to ask permission from the teacher when going to the bathroom to train students to respect elders and the same age both in madrasas and outside madrasas. In terms of social values, the madrasa head teaches teachers, staff, and students the meaning of caring for one another. The principal of the madrasa always pays attention to teachers and staff, because caring for one another will create a harmonious family atmosphere.